Denying Children's Visitation Rights To The Father According To The Syariah Court Civil Procedure Enactment (State of Selangor) 2003 - Binti Mohamed Zulkaffly*, Siti Nur Khamsani; Lubis, Syaddan Dintara (Universitas Syiah Kuala, 2023)
This study discusses the considerations carried out by the Sharia Court in Malaysia in the implementation of the order of the right of the child to visit the father in the case of denial of the father's right to see the child according to the Syariah Court Civil Procedure Enactment (State of Selangor) 2003. The type of research used is qualitative research with a normative jurisprudence approach based on the laws of Malaysia and Islamic law. The source of the research data uses secondary data, which includes the study of documents from the judgment of the syaria court. The researchers found that the right to the child is preferred to women because there is compassion and tenderness in caring for the child. In the case 10000-003-0008-2014 the researchers also found that children's rights can be lost if one breaches a court order that has been established. The results of this study show that according to good practices the sanction imposed is imprisonment for not more than six months or a fine not exceeding RM2,000 if she fails to show reasons or fail to satisfy the Court.